2019
DOI: 10.3171/2019.8.focus19543
|View full text |Cite
|
Sign up to set email alerts
|

Risks, costs, and outcomes of cerebrospinal fluid leaks after pediatric skull fractures: a MarketScan analysis between 2007 and 2015

Abstract: OBJECTIVESkull fractures are common after blunt pediatric head trauma. CSF leaks are a rare but serious complication of skull fractures; however, little evidence exists on the risk of developing a CSF leak following skull fracture in the pediatric population. In this epidemiological study, the authors investigated the risk factors of CSF leaks and their impact on pediatric skull fracture outcomes.METHODSTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It is common for patients with open skulls to have pathology in cranial CT. In the presence of a visible cranial pathology, cranial CT imagining is to investigate the presence of another pathology that is not visible below [14,15]. We think that there does not exist any difference between the patients that pathological findings were observed or not in the cranial CT statistically because this pathology was rarely observed in our patient group.…”
Section: Discussionmentioning
confidence: 88%
“…It is common for patients with open skulls to have pathology in cranial CT. In the presence of a visible cranial pathology, cranial CT imagining is to investigate the presence of another pathology that is not visible below [14,15]. We think that there does not exist any difference between the patients that pathological findings were observed or not in the cranial CT statistically because this pathology was rarely observed in our patient group.…”
Section: Discussionmentioning
confidence: 88%
“…6,7 Although CSF leaks can occur spontaneously 2,8 or iatrogenically after manipulation of the dura mater, postprocedural CSF leaks have been associated with the longer hospitalizations and more readmissions, and account for up to 10% of the total costs associated with neurosurgical procedures. 9,10 Previous studies have reported cost burdens of postoperative CSF leaks between $41,000 and 50,000 per affected patient. 9,[11][12][13] This increased health care resource utilization (HCRU) is important given the increasing scrutiny on medical expenditure in the United States.…”
mentioning
confidence: 99%
“…9,10 Previous studies have reported cost burdens of postoperative CSF leaks between $41,000 and 50,000 per affected patient. 9,[11][12][13] This increased health care resource utilization (HCRU) is important given the increasing scrutiny on medical expenditure in the United States.…”
mentioning
confidence: 99%